Master of Science in Medical Statistics Programme at Universiti Sains Malaysia: 20 Years Ongoing. - NORSA'ADAH, Bachok; YAACOB, Najib Majdi; ABDULLAH, Sarimah; KUEH Yee Cheng; AB HAMID, Siti Azrin; GHAZALI, Anis Kausar; NOR ARIFIN, Wan (Malaysian Journal of Medical Sciences, 2023)
Health and medical research are important parts of the curriculum of medical and health programmes in universities and play an important role in the functioning of organisations related to health care. There is a shortage of well-trained health and medical research statisticians. This article describes the courses and structure of the Master of Science in Medical Statistics programme at Universiti Sains Malaysia (USM), as well as the graduates' achievements. It is a 2-year programme that prepares qualified and competent graduates in statistical methods and data analysis for research in health and medical sciences. The Biostatistics and Research Methodology Unit, School of Medical Sciences, USM has been running the programme since 2003. It is currently the only medical statistics programme available in Malaysia. There have been 97 graduates since 2005, with an employment rate of 96.7% and a successful subsequent doctorate rate of 21.1%. Most of the students returned to their previous employments, mainly with the Ministry of Health of Malaysia and several others became lecturers, statisticians or research officers. The employability of graduates from this programme is very high and their professional future is bright. We hope our graduates will impart their knowledge and skills to the nation.